Desempenho muscular isocinético do complexo do ombro de indivíduos com hemiparesia crônica - Lucas Rodrigues Nascimento (2011)
Introduction: Muscular weakness is the most common impairment following stroke and has been shown to be significantly related to upper limb function. Information is still scarce regarding the magnitude of the weaknesses during dynamic conditions and the specific residual deficits of the paretic upper limb regarding the glenohumeral and the scapulothoracic muscles. Purpose: The present study compared the isokinetic muscular performance of the shoulder complex between individuals with and without stroke, as well as the patterns of distribution of the residual deficits during shoulder and scapular movements to better understand the determinants of the motor and functional upper limb impairments. Method: Twelve chronic stroke survivors and 12 healthy control subjects were recruited. Concentric measures of peak torque and work during the movements of shoulder external/internal rotations, shoulder flexion/extension, and scapular protraction/retraction, were randomly obtained by the Biodex isokinetic dynamometer at the angular velocity of 60º/s. For the individuals with stroke, the residual deficits related to the isokinetic work for the movements of scapular protraction, shoulder external rotationa, and shoulder flexion were also calculated. Repeated-measure ANOVAs were employed to investigate the main and interaction effects between the groups and sides and to compare the values of the residual deficits between the three evaluated movements. Results: The ANOVAS revealed that individuals with stroke demonstrated significant decreases in strength of the paretic shoulder, including during predominantly scapular movements, but no statistically significant decreases were observed for the non-paretic shoulder. The patterns of distributions of the residual deficits were similar for all assessed movements. Conclusions: The findings suggested that scapular weaknesses might significantly contribute to reduced performance of the shoulder complex. Individuals with chronic stroke may benefit from strengthening exercises directed to the scapular muscles, in addition to the glenohumeral muscles. Physical therapists should begin to focus their attention on the paretic upper limbs.